Penerapan Fungsi - Fungsi Microsoft Excel Dalam Pengelolaan Data Administrasi Perkantoran - Guntur Maha Putra; Rizaldi Rizaldi; Arridha Zikra Syah (Smart Education, 2021)
Abstract: As a Course Institution, acculturation and cooperation between supporting stakeh-olders is needed, to improve the existence of the institution by carrying out training training that supp-orts students and the general public to spread knowledge and skills through collaboration in the form of community service. This is also in accordance with what is stated in the Vision and Mission of LKP Pelita Media Kisaran. Starting from the above, the Community Service Te-am collaborates to carry out community service that is in line with the Vision and Mission of LKP Pelita Media which is useful as a portfolio of LKP activities and is also useful for service participants who take part in activities to improve the knowledge and skills of each participant in terms of scope of application of microsoft excel functions in office administration data management. Keywords:. Training; Excel; Community Service. Abstrak: Sebagai Lembaga Kursus maka diperlukan akulturasi dan kerjasama diantara stak-eholder yang mendukung, untuk meningkatkan eksistensi lembaga dengan melaksanakan pelatihan-pelatihan yang mendukung kepada peserta didik maupun masyarakat umum untuk menyebarkan pengetahuan dan keterampilan melalui kerjasama dalam bentuk pengabdian masy-arakat. Hal ini juga sesuai dengan yang termaktub di dalam Visi dan Misi LKP Pelita Media Kisaran. Berawal dari hal diatas maka Tim Pengabdian Masyarakat melakukan kerjasama untuk melakukan pengabdian kepada masyarakat yang sejalan dengan Visi dan Misi LKP Pelita Media yang berguna sebagai fortofolio kegiatan LKP dan juga berguna bagi peserta-peserta pengabdian yang mengikuti kegiatan untuk meningkatkan pengetahuan dan keterampilan masing-masing peserta dalam hal lingkup penerapan fungsi-fungsi microsoft excel dalam pengelolaan data administrasi perkantoran. Kata kunci: Pelatihan; Excel; Pengabdian Masyarakat.